Vegetative Propagation and Liquid Chromatography Mass Spectrometry (LCMS) Analysis of Indian Traditional and Endangered Plant Ulmus wallichiana using Air Layering Technology - Sahu, Neha; Tripathi, Karuna; Kanojia, Sanjeev; Arya, K. R. (Indian Forester, 2018)
Ulmus wallichiana is an endangered plant used for healing fractures in folk tradition of Uttarakhand Himalayas, India. Four bioactive metabolites for osteogenic activity have been isolated from the bark of this plant. Habitat degradation, biotic interferences and indiscriminate collection shows decline in species richness and total tree density in Indian Himalayas. This paper reports a fast and effective protocol for vegetative propagation of this plant using stem cuttings and air layering technologies along with Liquid Chromatography Mass Spectrometry (LCMS) analysis of developed plants. Different sizes of coppice shoots and hormonal concentrations i.e. Indole 3-acetic acid (IAA), Indole 3-butyric acid (IBA) and 2, 4 dichlorophenoxy acetic acid (2, 4-D) were used for standardization of optimal conditions for vegetative propagation. 3000 ppm IAA under 65-95% RH and 25-41Â°C temperature resulted in optimal number of 21.2 sprouts per explants and 6 % rooting through stem cuttings. However, 100 % rooting with an optimal number of 20.7 sprouts was achieved through air layering and it proved to be a better and more efficient technology. The developed plants have been successfully established and acclimatized in tropical environment Moreover, LCMS analysis of leaves from acclimatized plants showed higher peak abundance of quercetin-3-O-alpha-L- rhamnopyranoside, an important metabolite for osteogenic activity.